Balancing Curriculum and Pedagogy for Effective Technology Integration in Education - Adhikari, Toya Nath (Pragya Darshan प्रज्ञा दर्शन, 2025)
In contemporary educational discourse, the integration of technology into classroom settings has become an essential focus for educators worldwide. This article delves into the intricate relationships between the incorporation of technology and educational practices, with a particular emphasis on its effects on curriculum development and teaching methods. The study has two primary objectives: first, to investigate teachers' views and experiences regarding the influence of technology on curriculum design and teaching strategies; and second, to evaluate the challenges and opportunities that arise from embedding technology into classroom instruction. The research utilizes a comprehensive approach, including document analysis, field studies, and qualitative techniques like interviews. By reviewing existing literature and policy documents related to technology integration, the study establishes a theoretical framework. The results reveal that teachers generally perceive technology as a valuable asset for enhancing both curriculum design and instructional methods. While teachers recognize the potential of technology to improve teaching and boost student engagement, they also face challenges such as insufficient training and limited resources. There is a range of opinions among educators about the relative importance of technology in curriculum design compared to pedagogy. Some teachers view both aspects as equally important, while others emphasize either curriculum design or pedagogical methods as more critical in the context of technology integration.